Validasi Metode Spektrofotometri UV-VIS Untuk Analisis Formalin Menggunakan Pararosanilline HCL Pada Sampel Plasma Darah - Lindawati Setyaningrum (Jurnal Kesehatan dr. Soebandi, 2019)
Formaldehyde is as a solution containing 30% to 50% formalin with 0.5% to 15% methanol as a polymerization inhibitor. The use of formaldehyde is a sprayer of plants (3%), in order to get harvest is not decayed and withered easily, but it can result residues in plants and crop yields. It can affect in the body health when consumed. Formalin is very dangerous if it accumulates in the body. The safety threshold of formaldehyde in food that enters the body is 1.514 mg/day. Formaldehyde in the drinking water that can be tolerated is 0.1 ppm. Therefore, in this study, the aim was to identify the presence of formaldehyde residues in chili and human blood that consumes the yield of chili contaminated with formaldehyde.. This research was conducted to develop a method for detecting formaldehyde in chilli blood samples as a detection medium for body conditions which were then reacted with pararosanillin HCl. The results of the dark pink reaction followed by detection of the UV-VIS Spectrophotometer method at a wavelength of 539.0 nm. The results showed that this method was able to detect formaldehyde in blood samples with Y = 6.364x - 0.009 and the correlation coefficient (r) of 0.996 and Vx0 < 2, the detection limit was 0.069 ppm and the quantization limit was 0.230 ppm. The accuracy results give an average value of 88.173%. The precision value is expressed as a Relative Standard Deviation of 1.047%. Chili samples collected from around Mount Bromo were detected with the result of a range of formaldehyde concentrati